Nutrient contents in the organs and soil of young and mature Camellia oleifera C. Abel forests in China (Bangladesh Journal of Botany, 2022)
Nutrient contents in the organs and soil of the young and mature Camellia oleifera C. Abel were determined to study the demand and supply of nutrients for trees and soil, respectively. The young and mature C. oleifera forests were selected in the south suburb of Changsha, China. Results showed that the nutrient contents in the different tree organs of the mature forest in florescence period were in the order of leaf > flower > root > trunk > branch, and in the young forest were leaf > flower > branch > root > stem. In mature and young C. oleifera forests, the highest demand of macroelements in tree organs was for N and the lowest was for P. For microelements, the highest was for Mn and the lowest was for Cd. The soil nutrient supply in the mature and young C. oleifera forests consisted mainly the available N and K, and the available P in the least. The most macroelements were the total P and Ca, while the least was Mg. The nutrient demand of microelements was the highest for Fe and the lowest for Cd. The nutrient requirement of tree organs in mature and young C. oleifera forests was: young (2094.13 ± 656.79 mg/kg) > mature (1763.31 ± 419.27 mg/kg), while the soil nutrient supply was mature (2612.81 ± 756.68 mg/kg) > young (2312.99 ± 659.85 mg/kg). The nutrient content in the organs of the mature and young C. oleifera forest was high in the fructescence period as compared during the florescence period, while the soil nutrient supply was high in the florescence period than in the fructescence. Results could provide a scientific basis for the nutrition diagnosis and nutrition management of C. oleifera and other plants.Bangladesh J. Bot. 51(2): 359-369, 2022 (June)